The future of corporate real estate with data and analytics - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2016)
JLLrecently commissioned Penn Schoen Berland (PSB) to conduct in-depth interviewswith C-suite executives across the globe to understand their views on the rolethat data and analytics (D&A) plays in corporate real estate (CRE). Allparticipants in this series of interviews held overall responsibility for CREdecision making – at either the global or regional level – withintheir organisations.